Beyond money and gifts: Social capital as motivation for cross- generational dating among tertiary school female students in south west Nigeria (2010)
Cross generational dating is a global practice which has engaged the attention of scholars from across the social sciences and beyond. Despite the differences in the backgrounds of scholars, most have conceived cross generational dating as motivated simple by money and gifts and the satisfaction of immediate and short-term needs. This ethnographic study conducted among students on three Nigerian campuses shows that cross generational dating among Nigerian undergraduates students is motivated by the need to strengthen their social capital base. Younger partners date older ones in order to get connected for job and other placement: receive assistance with visa procurement and enhance their own in-group worth or rating. Older partners date younger ones to receive succor when their homes or jobs are troubled. Cross-generational dating, we discovered, is not a lone-ranging act but a practice that involves networking as well as different forms of pressure among ladies. Cross-generational dating may be a global phenomenon, but it wears local colors and carriers local nomenclatures. Contextualizing its study is therefore important to our understanding.